Normative Data for the Hayling and Brixton Tests in an Italian Population. (22nd August 2017) - Spitoni, Grazia Fernanda; Bevacqua, Sara; Cerini, Claudia; Ciurli, Paola; Piccardi, Laura; Guariglia, Paola; Pezzuti, Lina; Antonucci, Gabriella
Abstract: Objective: The Hayling and Brixton tests constitute a short test battery that quickly assesses verbal and spatial inhibition and flexibility. This battery has shown high construct validity and strong reliability in clinical and experimental settings. The aim of this study was to develop an Italian version of the Hayling and Brixton tests and obtain normative values. Method: We collected normative data from 301 healthy Italian participants aged between 16 and 94 years, taking into account all demographics. To maximize the sample size, we used the overlapping interval strategy. Adjusted scores for demographics were obtained by linear regression analysis. Results: The performance on the Hayling and Brixton tests was influenced by age and education. In particular, age affected verbal accuracy and response time on the Hayling Sentence Completion Test, whereas education only affected the former. Differently, the spatial component, as measured by the Brixton Spatial Anticipation Test, was shaped only by age, which decreased the number of correct responses. Conclusions: Our study provides normative data that have been adjusted for relevant demographics and percentile grids in an Italian population. Our data support the use of the Hayling and Brixton tests as a valid instrument for performing neuropsychological evaluations and longitudinal analyses of executive functions in clinical practice and for research purposes.